2022
DOI: 10.3389/fimmu.2022.855701
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation Following Traumatic Brain Injury: Take It Seriously or Not

Abstract: Traumatic brain injury (TBI) is associated with high mortality and disability, with a substantial socioeconomic burden. With the standardization of the treatment process, there is increasing interest in the role that the secondary insult of TBI plays in outcome heterogeneity. The secondary insult is neither detrimental nor beneficial in an absolute sense, among which the inflammatory response was a complex cascade of events and can thus be regarded as a double-edged sword. Therefore, clinicians should take the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 122 publications
0
24
0
Order By: Relevance
“…TBI triggers a rapid astrocytic response to brain trauma [ 12 , 46 49 ]. Although an increased number of astrocytes in post-trauma brains have been shown to seal the disrupted BBB to a certain extent [ 50 ], an excessive increase in the number of astrocytes may lead to an overabundance of pro-inflammatory responses that result in axonal injury, vascular disruption, and local ischemia in post-traumatic brains [ 47 , 49 ]. Previous studies have demonstrated that high levels of serum GFAP and S100B (an astrocyte marker) may function as predictors for increased mortality and unfavorable outcomes in TBI [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…TBI triggers a rapid astrocytic response to brain trauma [ 12 , 46 49 ]. Although an increased number of astrocytes in post-trauma brains have been shown to seal the disrupted BBB to a certain extent [ 50 ], an excessive increase in the number of astrocytes may lead to an overabundance of pro-inflammatory responses that result in axonal injury, vascular disruption, and local ischemia in post-traumatic brains [ 47 , 49 ]. Previous studies have demonstrated that high levels of serum GFAP and S100B (an astrocyte marker) may function as predictors for increased mortality and unfavorable outcomes in TBI [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recovery after mTBI varies among the patient population with some patients displaying better outcome measures than others. These differences in outcomes may be attributed to pre-existing conditions, genetic factors or concurrent polytrauma [ 36 , 74 ]. However, less attention has been paid to the effect of secondary insults during the chronic phase of mTBI on outcome measures, and the consequences are not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…The process is difficult to stop after the danger signal is no longer present, consequently, neutrophils indiscriminately cause brain tissue damage ( 33 , 34 ). Other studies have shown that the infiltration of T lymphocytes, monocytes, B cells and microglia after polarization plays a complex role in TBI, causing different effects, such as repair or aggravation of brain injury, at different periods ( 11 , 12 , 35 , 36 ). Therefore, the infiltration of inflammatory cells after TBI and downstream reactions play indispensable roles in TBI.…”
Section: Discussionmentioning
confidence: 99%